The Validity Assessment of E-Cadherin Expression to Differentiate Ductal and Lobular Type Invasive Breast Carcinoma - I Gusti Ayu Sri Mahendra Dewi (Journal of Global Pharma Technology, 2016)
Introduction: Currently, breast cancer is one of the leading causes of cancer related death in women worldwide. The diagnosis of breast cancer still depends on biopsy to determine the histopathological subtype and the nature of the cancer. However, the subtypes alone could not differentiate between lobular and ductal carcinoma. Therefore, this study aimed to evaluate the validity of E-cadherin expression as biomarker to differentiate ductal and lobular invasive breast carcinomas. Methods: An analytic observational cross sectional study was conducted using 47 biopsy samples of ductal and lobular type invasive breast carcinoma examined at Anatomical Pathology Laboratory Faculty of Medicine, Udayana University/ RSUP Sanglah Denpasar in 2017. The samples were evaluated using H & E staining while E-cadherin expression was examined by using Immunohistochemistry technique (IHC). Pearson chi-square was performed to analyze the data with p-value less than 0.05 was considered significant or valid. Result: Descriptive statistics showed that the samples were homogeneous in term of age between ductal and lobular types (p=0.668). Breast cancer was found to be more prevalent on the left breast compared to the right one in both in ductal and lobular types. IHC staining showed that E-cadherin expression was significantly lower in lobular types (9.1% positive) compared to ductal (60.0% positivity) and, thus, can be used to differentiate them (p=0.000). Conclusion: E-cadherin expression was a valid biomarker to differentiate ductal and lobular type invasive breast carcinoma. More comprehensive study with larger number of samples is required to assess the generality of this findingKeywords: E-cadherin, Breast carcinoma, Ductal type, Lobular type.